Information governance : concepts, strategies and best practices - Smallwood, Robert F., 1959- (John Wiley & Sons, Inc., 2014)
Proven and emerging strategies for addressing document and records management risk within the framework of information governance principles and best practices Information Governance (IG) is a rapidly emerging ""super discipline"" and is now being applied to electronic document and records management, email, social media, cloud computing, mobile computing, and, in fact, the management and output of information organization-wide. IG leverages information technologies to enforce policies, procedures and controls to manage information risk in compliance with legal and litigation demands, external.